(untitled) (Economics and region, 2024)
The aim of the study is to identify potential ways in which the management company of an industrial park can influence cohesion in Ukraine. The research is based on materials from UNIDO regarding industrial parks, EU materials on cohesion, Ukrainian legislation, and the works of both Ukrainian and foreign scholars. The analysis of the development status of industrial parks in Ukraine indicates that management companies demonstrate rather low performance in fulfilling their primary function of attracting residents. Furthermore, the organizational and legal structure of the management company appears to have little significant impact, as similar low performance is observed across various forms. At this point, it’s quite hard to track the impact of management companies on cohesion. The examination of various potential functions of management companies has revealed their capacity to contribute to cohesion. This applies to both the external effects stemming directly from economic activities within the industrial park and the potential terms of agreement between the management company and the industrial park residents.